Landscape and environmental factors and ranavirus epidemiology in an amphibian assemblage, East Bay, California - Tornabene, Brian J; Blaustein, Andrew R; Briggs, Cheryl J; Calhoun, Dana M; Johnson, Pieter T J; McDevitt-Galles, Travis; Rohr, Jason R; Hoverman, Jason T (Supplement to: Tornabene, BJ et al. (2018): The influence of landscape and environmental factors on ranavirus epidemiology in a California amphibian assemblage. Freshwater Biology, 63(7), 639-651, https://doi.org/10.1111/fwb.13100, 2017)
Aim To quantify the influence of a suite of landscape, abiotic, biotic, and host-level variables on ranavirus disease dynamics in amphibian assemblages at two biological levels (site and host-level). Location Wetlands within the East Bay region of California, USA. Methods We used competing models, multimodel inference, and variance partitioning to examine the influence of 16 landscape and environmental factors on patterns in site-level ranavirus presence and host-level ranavirus infection in 76 wetlands and 1,377 amphibian hosts representing five species. Results The landscape factor explained more variation than any other factors in site-level ranavirus presence, but biotic and host-level factors explained more variation in host-level ranavirus infection. At both the site- and host-level, the probability of ranavirus presence correlated negatively with distance to nearest ranavirus-positive wetland. At the site-level, ranavirus presence was associated positively with taxonomic richness. However, infection prevalence within the amphibian population correlated negatively with vertebrate richness. Finally, amphibian host species differed in their likelihood of ranavirus infection: American Bullfrogs had the weakest association with infection while Western Toads had the strongest. After accounting for host species effects, hosts with greater snout-vent length had a lower probability of infection. Main conclusions Strong spatial influences at both biological levels suggest that mobile taxa (e.g., adult amphibians, birds, reptiles) may facilitate the movement of ranavirus among hosts and across the landscape. Higher taxonomic richness at sites may provide more opportunities for colonization or the presence of reservoir hosts that may influence ranavirus presence. Higher host richness correlating with higher ranavirus infection is suggestive of a dilution effect that has been observed for other amphibian disease systems and warrants further investigation. Our study demonstrates that an array of landscape, environmental, and host-level factors were associated with ranavirus epidemiology and illustrates that their importance varies with biological level.